Infographic. A systematic review and meta-analysis of the effect of ß-alanine supplementation on exercise capacity and performance - Saunders, B.; Virgile, A.; Elliott-Sale, K. J.; Artioli, G. G.; Swinton, P. A.; Dolan, E.; Roschel, H.; Sale, C.; Gualano, B. (British Journal of Sports Medicine, 2020)
These meta-analytical data allow coaches and athletes to make informed decisions as to the likelihood of an ergo-genic effect with ß-alanine supplemen-tation based on their specific exercise demands, with those performing high-in-tensity tasks between 30s and 10min most likely to benefit. Individuals can safely supplement daily with ß-alanine for up to 24 weeks at a dose of 3.2-6.4g/day ingested at several time points throughout the day (0.8-1.6g every 3-4hours) to avoid acute side effects (ie, paraesthesia).